1996
DOI: 10.1016/0885-3924(95)00168-9
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal morphine for analgesia in children undergoing selective dorsal rhizotomy

Abstract: Selective dorsal root rhizotomy is performed for relief of spasticity in children with cerebral palsy. Postoperative pain relief can be provided by intrathecal morphine administered at the time of the procedure. We sought to define an optimal dose of intrathecal morphine in children undergoing selective rhizotomy, through a randomized, double-blinded prospective trial. After institutional approval and parental written informed consent, 27 patients, ages 3-10 years, were randomized to receive 10, 20, or 30 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 13 publications
0
30
1
Order By: Relevance
“…alone gave itching in 56% of children (34). The general incidence of pruritus found in this study was low compared with other studies (7,9,31) and one reason could be our use of ondansetron to treat PONV. Previous studies have shown that ondansetron is effective in treating spinal morphine‐induced pruritus (16,26,35), and all children in the low‐dose group and 73% of the children in the high‐dose group received ondansetron.…”
Section: Discussioncontrasting
confidence: 80%
“…alone gave itching in 56% of children (34). The general incidence of pruritus found in this study was low compared with other studies (7,9,31) and one reason could be our use of ondansetron to treat PONV. Previous studies have shown that ondansetron is effective in treating spinal morphine‐induced pruritus (16,26,35), and all children in the low‐dose group and 73% of the children in the high‐dose group received ondansetron.…”
Section: Discussioncontrasting
confidence: 80%
“…IT morphine has not been found to affect the haemodynamic parameters ( 5). One could expect a lower systemic blood pressure in the bupivacaine/morphine group due to the sympathetic blockade.…”
Section: Discussionmentioning
confidence: 99%
“…The use of morphine IT has been shown to provide a long duration of postoperative analgesia and it has been described for a variety of surgical procedures (4,5,8±11). Harris et al (4) report the duration of analgesia to be 3±48 h and, in the study by Dews et al (5), the pain relief was 1±15 h depending on the dose. The half-life of morphine in cerebrospinal¯uid (CSF) is similar in plasma (12).…”
Section: Discussionmentioning
confidence: 99%
“…Our experience is that postoperative pain treatment in these children can be demanding, not only due to postincision pain from the lumbar laminotomy, but also due to dysesthesia of the lower extremities caused by manipulation of the nerve rootlets [8,24,25,26,27,28,29,30]. During the 1980s, it is most probable that these children were treated with conventional intravenous and/or oral regimes.…”
Section: Discussionmentioning
confidence: 99%
“…During the last two decades, various pain treatment strategies have been published for children undergoing SDR. Both ED [25, 29] and IT opioids [28, 30, 31] have been used as an effective and safe pain therapy. Continuous intravenous morphine infusion has been reported as an option [27].…”
Section: Discussionmentioning
confidence: 99%